Political writings : contributions to justice and commonweal 1883-1890 - Morris, William (Thoemmes Press, 1994)
William Morris, the famous artist and designer, was one of the most prominent late-Victorian socialists. Not only did he lecture on many hundreds of occasions for the Social Democratic Federation and the Socialist League, but he also excelled as a political journalist. Between 1883 and 1890 he contributed almost 500 signed articles to two of the most important socialist papers: "Justice" and "Commonweal". Amongst the works he serialized in "Commonweal" were his two well-known socialist romances "A dream of John Ball" and "News from Nowhere", and his narrative poem "The Pilgrim of Hope". The present collection gathers together in chronological order all the important essays from the period 1883 to 1890, along with "Socialism from the Root Up" and the four political dialogues which Morris wrote to entertain the readers of "Commonweal". Together these offer a new insight into the political philosophy of one of the most influential thinkers of the Victorian Age.